Baba Tukty Shashty Aziz: myth and reality - Karatyshkanova, K.; Zhandarbek, Z.; Maldybek, А. (Eurasian Journal of Religious Studies, 2025)
Saints and holy places occupy a special place in the spiritual and cultural identity of the Kazakh people. In the Kazakh understanding, holy and sacred places are perceived as the main spiritual centers that connect the human spirit with the Spiritual world and act as an integral part of spiritual and cultural identity. Most researchers are familiar with the concept of “saint”, but few know the personality of Saint Baba Tukta Shashta Aziz, who symbolizes a mythical image and a significant figure in the history of the Golden Horde. The idea of ​​​​scientific research is to study the role of holy places in achieving unity with the spiritual world by humanity, including showing the participation of Baba Tukty Shashty Aziz in this holiness. Therefore, the main goal of this article is to analyze the legends and historical data about Baba Tukty Shashty Aziz, to identify their connection with historical reality, to show their place in the historical destiny of the Kazakh people. The scientific and practical significance of the work lies in identifying the differences between mythical images and historical reality, which allows for a deeper understanding of how religious and cultural narratives shape public consciousness. In the article, the phenomenon of the holiness of Baba Tukty Shashty Aziz was described and interpreted using the phenomenological method, and the theoretical and practical conclusions of this study were determined by comparison. The role of Baba Tukty Shashty Aziz in the development of Kazakh statehood and spirituality has not been fully considered or studied in scientific literature, which increases the value of this study and its contribution to the development of religious studies knowledge.Keywords: Baba Tukty Shashty Aziz, Saint, Golden Horde, Sufism, Spiritual world, Myth.